An Analysis of Diversity Inventory of Typical Sciences of the Donggo Tribe in Science Learning Based on an Ethnoscience Approach in Elementary Schools - nurwalidainismawati, Nurwalidainismawati (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to identify and examine various forms of ethno-scientific activity from the customs of the Donggo people in the form of a science inventory that can be used in learning science in elementary schools. The method in this study is a qualitative method using an ethnoscience approach. The data collection process was carried out through open interviews with the indigenous people of Donggo (Bima) in order to obtain inventory data so that it could be further analyzed and described. As a result, original science which is a cultural heritage by the Donggo people can be used as a recommendation for learning science, especially in class IV, which can be taught scientifically to elementary school students. on plant material